Exploiting genetic variation for lime-induced iron-deficiency chlorosis in groundnut (Arachis hypogaea) - MANN, ANITA; SINGH, A L; KUMAR, ARVIND; PARVENDER, PARVENDER; OZA, SHUBHANGI; GOSWAMI, NISHA; CHAUDHARI, VIDYA; PATEL, C B; ZALA, P V (The Indian Journal of Agricultural Sciences, 2023)
The screening of 114 groundnut (Arachis hypogaea L.) genotypes (61 advanced breeding lines and 53 released cultivars) was undertaken in the screening plots to identify the iron-efficient genotypes tolerant to lime-induced ironchlorosis. The crop was grown and the intensity of chlorosis of top five leaves was rated for visual chlorotic rating (VCR) score on a 1-5 scale and the percentage of plants showing deficiency symptoms at 10, 20, 30 and 65 days after emergence during the cropping season. The tolerant genotypes had shown significantly lower VCR, higher Soil Plant Analysis Development (SPAD) chlorophyll meter reading and chlorophyll values, active Fe, and high yield compared to the sensitive ones. The correlation of visual chlorosis range with SPAD, chlorophyll and available iron content along with the mineral nutrients like, Fe, Zn, Mn, K, and P clearly identified the groundnut genotypes as tolerant, moderately tolerant and sensitive to iron chlorosis. Based on various parameters, out of 114 genotypes, 22 were grouped as tolerant, 48 moderately tolerant, 32 normal and 12 sensitive. Maximum variability was obtained in groundnut genotypes for Fe and fodder weight.